2017
DOI: 10.1038/srep44129
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteogenesis and angiogenesis by mesoporous hydroxyapatite microspheres-derived simvastatin sustained release system for superior bone regeneration

Abstract: Biomaterials with both excellent osteogenic and angiogenic activities are desirable to repair massive bone defects. In this study, simvastatin with both osteogenic and angiogenic activities was incorporated into the mesoporous hydroxyapatite microspheres (MHMs) synthesized through a microwave-assisted hydrothermal method using fructose 1,6-bisphosphate trisodium salt (FBP) as an organic phosphorous source. The effects of the simvastatin-loaded MHMs (S-MHMs) on the osteogenic differentiation of rat bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 59 publications
1
58
0
Order By: Relevance
“…While osteoblasts and fibroblasts can be observed within the ROB‐laden PEG4K–Clay scaffolds, new bone can also be clearly observed around and within the scaffolds. H&E staining22, 23 was used to further validate the Giemsa staining results (Figure 5). The results were consistent with the data collected from micro‐CT and new bone labeling analyses, verifying that PEG4K–Clay nanocomposite hydrogel scaffolds can stimulate new bone formation, and that the loading of exogenous cells into the scaffolds through 3D‐bioprinting has further positive implications for bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While osteoblasts and fibroblasts can be observed within the ROB‐laden PEG4K–Clay scaffolds, new bone can also be clearly observed around and within the scaffolds. H&E staining22, 23 was used to further validate the Giemsa staining results (Figure 5). The results were consistent with the data collected from micro‐CT and new bone labeling analyses, verifying that PEG4K–Clay nanocomposite hydrogel scaffolds can stimulate new bone formation, and that the loading of exogenous cells into the scaffolds through 3D‐bioprinting has further positive implications for bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Hematoxylin (Sigma‐Aldrich, St. Louis, USA) and eosin (C0105, Beyotime Biotechnology, Shanghai, China) (H&E) staining22 and Goldner's staining24 were used to detect the specific tissue response to the implanted materials. Images were taken under the fluorescence microscope (Olympus, BX53, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to DRP1, MCU is also involved in this process, and its downregulation results in mitochondria-mediated defective efferocytosis in the Ldlr −/− /Drp1 −/− mice. These findings were proven by dexamethasone as an inducer of thymocyte apoptosis and resulted in defective efferocytosis [125]. Park et al have shown that the mitochondrial membrane uncoupling protein 2 (UCP2) was upregulated in phagocytes engulfing ACs [126].…”
Section: Mitochondrial Fission and Related Factors In Efferocytosis Amentioning
confidence: 99%
“…Accordingly, the factors that influence the continued clearance of ACs by phagocytes are vital for efficient efferocytosis [121]. Degradation of the ingested AC and vesicular trafficking in the phagocyte are essential for engulfing another AC [125]. Mitochondrial fission facilitates appropriately digestion of AC-derived debris and vesicular trafficking, both of which are Ca 2+ -dependent in mice [125].…”
Section: Mitochondrial Fission and Related Factors In Efferocytosis Amentioning
confidence: 99%
See 1 more Smart Citation